Analysis of Regional Financial Management on Economic Growth in the Era of Fiscal Decentralization in Makassar City - Aldea Musdayanti; Citra Ayni; Sri Astuty; Regina Regina; Basri Bado (Jurnal Ilmu Ekonomi JIE, 2025)
This study aims to determine how regional financial management performance during the Fiscal Decentralization Era affects the economic growth of Makassar City from 2013 to 2024. This study uses a quantitative descriptive analysis method, with calculations of the financial independence ratio, PAD effectiveness ratio, expenditure efficiency ratio, and revenue growth ratio, and continues with multiple linear regression. The results of the study show that the financial independence ratio is at an average of 65.26% which means participation; the PAD effectiveness ratio is at an average of 83.7% which means quite effective; the expenditure efficiency ratio is at an average of 98.8% which means less efficient, and the revenue growth ratio is at 5.66% with a moderate category. The results of statistical tests show that there is a positive and significant influence of the regional financial independence ratio and the PAD effectiveness ratio on economic growth, whereas the expenditure efficiency ratio and the revenue growth ratio have a negative and insignificant influence on economic growth in Makassar City.